1991
DOI: 10.1084/jem.174.5.1001
|View full text |Cite
|
Sign up to set email alerts
|

An unusual lineage of alpha/beta T cells that contains autoreactive cells.

Abstract: In male mice that express a transgenic alpha/beta T cell receptor (TCR) specific for a male-specific peptide presented by class I Db major histocompatibility complex (MHC) molecules, we describe an unusual lineage of alpha/beta T cells that are thymus dependent but do not require selection by Db MHC molecules on thymic epithelium in the absence of the specific peptide (positive selection). These cells express the transgenic alpha/beta TCR and have the CD4-8- or CD4-8low phenotype. Cells with the latter phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
127
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(137 citation statements)
references
References 22 publications
8
127
2
Order By: Relevance
“…However, they differ from conventional memory T cells in that they are more refractory to activation by antigen compared with naive T cells. 7,8 von Boehmer et al 5 have shown that the development of CD8 lo cells is thymus dependent, since the cells are not found in male H-2 b H-Y nude mice. By contrast, Yamada et al 6 found that CD8 lo cells developed normally in thymectomized male but not female H-2 b mice.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they differ from conventional memory T cells in that they are more refractory to activation by antigen compared with naive T cells. 7,8 von Boehmer et al 5 have shown that the development of CD8 lo cells is thymus dependent, since the cells are not found in male H-2 b H-Y nude mice. By contrast, Yamada et al 6 found that CD8 lo cells developed normally in thymectomized male but not female H-2 b mice.…”
Section: Introductionmentioning
confidence: 99%
“…3 Interestingly, there is a population of CD8 ϩ T cells, which express a low level of CD8 (referred to as CD8 lo ), that are resistant to deletion in male mice. 4,5 The CD8 lo cells are selfreactive, as they expand after transfer into male but not female H-2 b nude mice. 5 These cells express high levels of CD44 5 and interleukin-2 receptor ␤ (IL-2R␤; CD122) 6 that are characteristic of memory T cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of an § / g TCR + CD4 -CD8 -T cell population is a unique feature of TCR transgenic mice [21][22][23]. While different mechanisms may explain how such cells arise in these animals [21,23], it is likely that the current study could simply represent another example of TCR transgenic animals containing these CD4 -CD8 -T cells.…”
Section: Altered Development Of Cd4 + Dotcr + T Cells Bearing Alternamentioning
confidence: 86%
“…Initially, this finding could have been misinterpreted because the premature expression of the transgenic TCR leads to lineage diversion of some double negative (DN) cells into the DNgd lineage [26][27][28]. This was taken as evidence that in these mice there was only a developmental arrest at the DN stage rather than deletion of DP thymocytes [29].…”
Section: Intrathymic Deletion: Where and When?mentioning
confidence: 99%